Relationship between COVID-19-specific occupational stressors and mental distress in frontline and non-frontline staff. Issue 8 (August 2022) - Hazumi, Megumi; Matsui, Kentaro; Tsuru, Ayumi; Otsuki, Rei; Nagao, Kentaro; Ayabe, Naoko; Utsumi, Tomohiro; Fukumizu, Michio; Kawamura, Aoi; Izuhara, Muneto; Yoshiike, Takuya; Kuriyama, Kenichi
Abstract: This study investigated the difference in the severity of mental distress and factors contributing to mental distress in frontline and non-frontline healthcare professionals during the coronavirus disease (COVID-19) pandemic. A cross-sectional web-based survey of medical staff collected by snow-ball sampling was performed in Japan in October 2020 using the Kessler Psychological Distress Scale (K6) as an outcome measure for mental distress. Originally developed items asking about the degree of change in psychological and physical burdens, COVID-19-related fear, and experience of discrimination were obtained. The median score of the K6 was 7 in the frontline staff group (n = 86) and 6 in the non-frontline staff group (n = 504), without a statistically significant difference. Multiple regression analyses showed that among the participants, an increase in psychological burden and COVID-19-related fear was significantly associated with mental distress in both groups. Experience of discrimination was significantly associated with mental distress only in the frontline staff group. However, an increase in physical burden was significantly associated with mental distress only in the non-frontline staff group. The results indicate that the factors contributing to mental distress between frontline and non-frontline staff can be different, although the severity of mental distress is comparable between them. Highlights: This study assessed COVID-19 related occupational stressors in medical staff. Mental distress associated with fear of COVID-19 in medical staff. Discrimination associated with mental distress in frontline staff. Physical and psychological burden correlated in non-frontline staff. Interventions enhancing interpersonal contact can be helpful for medical staff. Abstract : COVID-19; Health care worker, Frontline, Non-frontline, Mental distress.